Babes [videorecording (DVD)] - Glazer, Ilana; Glazer, Ilana; Rabinowitz, Josh; Buteau, Michelle; Lynch, John Carroll, 1963-; Platt, Oliver; Bernhard, Sandra; James, Stephan, 1993-; Minhaj, Hasan, 1985- (Decal, 2024)
Babes follows childhood best friends Eden and Dawn, now in different phases of adulthood. When single Eden decides to have a baby on her own after a one-night stand, their friendship faces its greatest challenge.